Efficacy of Manual Ventilation Techniques During Cardiopulmonary Resuscitation in Dogs - Hopper, Kate; Rezende, Marlis L.; Borchers, Angela; Epstein, Steven E. (Frontiers in Veterinary Science, 2018)
The efficacy of ventilation of dogs during cardiopulmonary resuscitation (CPR) with a tight fitting face mask or mouth-to-nose rescue breathing has not been evaluated. 24 purpose bred research dogs Dogs were randomized to be ventilated by cuffed orotracheal tube, tight fitting face mask, mouth-to-nose breathing or compressions only during CPR (n=6 in all groups). Orotracheal tube and face mask ventilation was performed on room air. Chest compressions were performed during the experimental procedure. Arterial blood gases were performed prior to euthanasia (baseline), at 3 minutes and at 6 minutes of CPR. PaO2 and PaCO2 were compared for each time point and each group. There was no difference in PaO2 or PaCO2 between groups at baseline. At 6 minutes all groups had a significantly higher PaCO2 (P 0.005) and the facemask and compression only groups had a significantly lower PaO2 (P<0.02 ) when compared to the orotracheal tube group. There was no difference between the PaO2 of the mouth-to-nose group compared to the orotracheal tube group at 3 or 6 minutes. Gastric distension, regurgitation, gas leakage around the mouth and ineffective breaths were all noted in both the face mask and mouth-to-nose group. The results of this study supports that orotracheal intubation is the preferred technique for ventilation during CPR in dogs. When orotracheal intubation is not possible, face mask ventilation or mouth-to-nose ventilation would be reasonable alternatives. When oxygen supplementation is available, face mask ventilation is likely to be superior. Appropriate training for both face mask and mouth-to-nose ventilation techniques is recommended.